The Economics of Networking - Sørensen, Olav Jull (Ekonomika, 2002)
Networks are finally accepted as a governance structure of their own. They are not a transitory and unstable form, which eventually will become a hierarchy or a market. In fact networks seem to be the most important way to organise economic activity within the framework of globalisation, the knowledge society and the deep technological changes taking place. Networks seem to appear whenever turmoil or even chaos prevails. The Network Theory contests classical undersocialised theories by viewing economic and business activity as socially embedded. Business activity is conducted in a co-operative and trustful atmosphere. Writings on the Network Theory, however, tend to be oversocialised. Economic activity is assumed but not explicitly dealt with. This paper aims to discuss classical economic issues (profit objectives, transaction costs, optimal decision making, uncertainty and risk, innovation etc.) and how the Network Theory accommodates these classical economic and business issues. At the end of the paper, implications for management and research are briefly outlined, indicating that with the Network Theory coming of age, it is essential to more explicitly formulate the theory as an economic theory which strikes a better balance between the economic and the human side.